OPTIMASI KADAR N DAN P UNTUK PRODUKSI BIOMASSA DAN ASTAKSANTIN PADA SPIROGYA SP. MENGGUNAKAN ANALISIS RESPONSE SURFACE METHODOLOGY DAN PEMODELAN KINETIKA - Yulius C P, Malvin
Astaxanthin is a type of antioxidant in the form of a red pigment which belongs to the carotenoid secondary metabolite group. Astaxanthin is used in various industries, such as nutraceutical, cosmetic, and food. These compounds can be produced by algae, including from Spirogyra sp. which is a potential green macroalgae commonly found in Indonesian freshwater. Astaxanthin levels in Spirogyra sp. are relatively low so that a suitable cultivation method is needed to increase the production of astaxanthin. The purpose of this study was to determine the optimum variation of N and P levels for biomass and astaxanthin production in Spirogyra sp., and to analyze the optimum conditions using Response Surface Methodoloy (RSM) analysis and modeling with Logistics, Monod, and Luedeking Piret equations. Cultivation was carried out for 14 days on modified 25% BG medium with variations in N/P levels of 1.1/0.06; 2.2/0.06; 6.6/0.06; 4.4/0.03; 4.4/0.06; and 4.4/0.09 mM. Data were collected every 3 days in the form of dry weight of biomass, nitrate levels, and astaxanthin levels. The dry biomass was extracted by maceration. The extract was then analyzed using the HPLC with a C-18 reverse phase column, eluent of HPLC grade of methanol: aqueous (95:5 v/v), flow rate of 1 mL/minute and detection using UV ? 482 nm. The results showed that the highest accumulation of biomass was found at levels of N 1.1 mM and P 0.06 mM, as much as 307 mg dry weight with a growth rate of 0.1645 day-1. The highest astaxanthin levels were found at levels of N 1.1 mM and P 0.06 mM as much as 0.254 mg/g dry weight. RSM analysis with dry weight data mapping resulted in optimum NaNO3 and K2HPO4 concentrations at 100 mg/L and 15 mg/L. Logistics, Monod, and Luedeking-Piret modeling were carried out to obtain models from experimental data and predict optimal conditions for biomass cultivation in all variations of N and P levels and obtained several parameters in the form of growth rate of Spirogyra sp. of 0.08 to 0.17 day-1, the largest value of ?max at 0.1 day-1,value of ? from -1.7 to 1.8, and value of ? at -0.01±0.02. The highest astaxanthin productivity was found in variations in the levels of N 1.1 mM and P 0.06 mM, at 30.48 kg/ha/year.